What Pre-service Teacher Student Said Arranging and Publishing Blog Page - Tuluk, Güler (Elsevier BV, 2014)
AbstractIn this study, aim was to provide pre-service mathematics student teachers with a new learning and teaching experience while they were playing two roles as learners and teachers within a arranging and publishing blog environment. The question of study was to investigate how a blog-mathematics course affected the ideas pre-service mathematics student teachers as a result of their experiences within that environment. The study showed that participants were: Willing toimplement blog construction activities about geometry lessons for their students; Willing to develop new methood sands trategies for conceptual geometry lessons; and to gain new perspectives on developing a blog as a teacher; Able to discover the importance of good team communication and appreciate developing a product for their students.Willing to uses ocial soft ware (wikipedia, wiktionaryetc.)It was concluded that the mathematic thinking processmay be improved as a result of preaparing a blogpage in mathematics teaching.Thus by considering the positive effects of blog page instruction, wesuggest that thephylosophical aspects and dynamics behind instructional technology should be clearly understood by teachers. Therefore educational faculties need to perform more research in this field.
Keywords: Blog prepare; geometry teaching; Instructional techonology; 4. Education